2019
DOI: 10.3390/w11122491
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Water Insecurity: A Structural Equation Approach for Female Headed Households in South Africa

Abstract: Intricacies between women and water are central to achieving the 2030 Sustainable Development Goals (SDGs). Gender equality and women empowerment is a key driver in ending hunger and poverty as well as improve water security the study sought to identify and provide pathways through which female-headed households were water insecure in South Africa. Secondary data collected during the 2016 General Household Survey (GHS) was utilised, with a sample of 5928 female-headed households. Principal Component Analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
8
0
4
Order By: Relevance
“…Te oordeel aan die uiteenlopende waterverwante kwessies in Suid-Afrika, is dit duidelik dat watersekuriteit 'n dringende maatreël is wat die regering moet aanspreek (Soyapi, 2017). Verskeie outeurs soos Ngarava et al (2019), Meissner et al (2018) en het studies gedoen oor watersekuriteit in Suid-Afrika, wat gemengde resultate op die vlak van watersekuriteit aandui.…”
Section: Inleidingunclassified
See 3 more Smart Citations
“…Te oordeel aan die uiteenlopende waterverwante kwessies in Suid-Afrika, is dit duidelik dat watersekuriteit 'n dringende maatreël is wat die regering moet aanspreek (Soyapi, 2017). Verskeie outeurs soos Ngarava et al (2019), Meissner et al (2018) en het studies gedoen oor watersekuriteit in Suid-Afrika, wat gemengde resultate op die vlak van watersekuriteit aandui.…”
Section: Inleidingunclassified
“…Huishoudelike sosio-ekonomiese eienskappe het min aandag gekry in terme van watersekuriteit op huishoudelike vlak in Suid-Afrika (Sinyolo et al, 2014). 'n Klein aantal studies deur Ngarava et al (2019) en Sinyolo en Mudhara (2014), het probeer om op die sosio-ekonomiese aspekte van watersekuriteit in Suid-Afrika te fokus. Die meeste van hierdie studies was egter óf homogeen (Ngarava et al 2019), wat op die hele land as geheel gefokus het, óf ruimtelik anders gefokus op sekere gebiede, soos 'n studie deur Meissner et al (2018), wat na Sekhukhune en eThekwini Plaaslike Munisipaliteite gekyk het.…”
Section: Inleidingunclassified
See 2 more Smart Citations
“…Previous studies discovered that, among others, community social status influences access and management to clean water (Ngarava et al, 2019), investment growth can affect the expansion of settlements in coastal areas and have an impact on water quality degradation (Hoque et al, 2019), land use for agriculture is more optimal when carried out in rural areas with consideration of market access and better water availability (Harmanny & Malek, 2019), the majority of the poor finds it difficult to access clean water pipes due to cost issues (Carrard et al, 2019),increasing the ability of the community to manage water resources is needed to reduce social barriers in the use of clean water (Panthi et al, 2019). Meanwhile, this study found the role of access and capacity of the community in reducing the potential for lack of clean water.…”
Section: Components Of Water Povertymentioning
confidence: 99%